The Ordovician conodont Trapezognathus Lindström, 1955 in the Andean Basin, Argentina - Carlorosi, Josefina Maria Teresa (2013)
The central Andean basin is characterized by the presence of Ordovician deposits, distributed mainly in Northwestern Argentina. Conodonts from the Lower and Middle Ordovician were recovered from several outcrops from the Trapezognathus diprion Zone, Baltoniodus cf. B. triangularis, Baltoniodus triangularis Zone, and among them the genus Trapezognathus is highlighted. This paper describes and illustrates two species of this genus: T. diprion (Lindström) and T. quadrangulum Lindström. In addition we report that the conodont association suggests faunal affinity with Baltica and South China.